2013
DOI: 10.1016/j.bbmt.2013.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Expression of Enteric Antimicrobial Proteins in Intestinal Graft-Versus-Host Disease

Abstract: We recently demonstrated that expression of α-defensins, the major antimicrobial peptides produced by Paneth cells, was severely suppressed in mice with graft-versus-host disease (GVHD). In this study, we found that antibacterial lectin, regenerating islet-derived IIIγ (RegIIIγ) was upregulated in villous enterocytes, thus demonstrating the reciprocal control of enteric antimicrobial proteins in GVHD. Upregulation of RegIIIγ was mediated by a mechanism independent upon radiation-induced intestinal tract damage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…Reg3β and Reg3γ can be produced by crypt epithelium and mature enterocytes (272). Furthermore, mice with Paneth cell deficiency due to GVHD demonstrate increased expression of Reg3γ, indicating that enterocytes are potent sources of intestinal antimicrobials (273). Additionally, we have found that IL-22R is expressed on Lgr5 + intestinal stem cells (137), although the functional significance of this is unknown.…”
Section: ) Target Tissues: Pathophysiology and Regenerative Biologymentioning
confidence: 99%
“…Reg3β and Reg3γ can be produced by crypt epithelium and mature enterocytes (272). Furthermore, mice with Paneth cell deficiency due to GVHD demonstrate increased expression of Reg3γ, indicating that enterocytes are potent sources of intestinal antimicrobials (273). Additionally, we have found that IL-22R is expressed on Lgr5 + intestinal stem cells (137), although the functional significance of this is unknown.…”
Section: ) Target Tissues: Pathophysiology and Regenerative Biologymentioning
confidence: 99%
“…Although production of Reg3a and its murine homolog Reg3g have previously been attributed to Paneth cells, it is clear that other non-Paneth-cell IECs produce Reg3g after experimental HCT in mice. 57,63 This potentially explains how Reg3 levels can be elevated despite the loss of Paneth cells that has been observed in the settings of experimental 57,64,65 and clinical 66 GVHD. Importantly, loss of Paneth cells was found to be a poor prognostic finding in clinical cases of intestinal GVHD.…”
mentioning
confidence: 99%
“…Why plasma levels of Reg3α correlate with GVHD severity remains an open question, but it may reflect either epithelial cell damage or may be a physiological response to intestinal injury and compromised barrier function. While production of Reg3α and its murine homologue Reg3γ has previously been attributed to Paneth cells, it is clear that other non-Paneth-cell IECs produce Reg3 after experimental BMT in mice 57,63 . This potentially explains how Reg3 levels can be elevated despite the loss of Paneth cells that has been observed in the settings of experimental 57,64,65 and clinical 66 GVHD.…”
Section: Components and Function Of The Intestinal Epithelium In The mentioning
confidence: 99%